2018
DOI: 10.32607/20758251-2018-10-4-95-99
|View full text |Cite
|
Sign up to set email alerts
|

The TLR4 Agonist Immunomax Affects the Phenotype of Mouse Lung Macrophages during Respiratory Syncytial Virus Infection

Abstract: In the study, the effect of the TLR4 agonist Immunomax was investigated in vitro and in vivo. In particular, Immunomax was shown to polarize mouse bone marrow macrophages from the M0 and M2 states into the M1 state (ARG1 and iNOS mRNA expression levels were used to identify the mouse M1 and M2 phenotypes). Next, we investigated the prophylactic antiviral effect of Immunomax in both a model of mouse respiratory syncytial virus (RSV) infection and a model of RSV-induced bronchial asthma (BA) exacerbation. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Asthma is a chronic disorder of the airways associated with episodes of bronchial constriction, mucus production, and immune cell infiltration. The inflammation associated with disease can be driven by allergic or non‐allergic mechanisms, where the activation of Toll‐like receptors (TLRs) on epithelial cells and macrophages regulates the initial nature of the innate inflammatory response . TLR4 activation in response to bacterial components, such as lipopolysaccharide (LPS), will drive nuclear factor (NF)‐κB‐driven inflammatory programming towards IL‐1β, IL‐6, and TNF‐α production in macrophages, promoting the activity of type 1 (M1)‐resident populations and neutrophilic inflammation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Asthma is a chronic disorder of the airways associated with episodes of bronchial constriction, mucus production, and immune cell infiltration. The inflammation associated with disease can be driven by allergic or non‐allergic mechanisms, where the activation of Toll‐like receptors (TLRs) on epithelial cells and macrophages regulates the initial nature of the innate inflammatory response . TLR4 activation in response to bacterial components, such as lipopolysaccharide (LPS), will drive nuclear factor (NF)‐κB‐driven inflammatory programming towards IL‐1β, IL‐6, and TNF‐α production in macrophages, promoting the activity of type 1 (M1)‐resident populations and neutrophilic inflammation.…”
Section: Introductionmentioning
confidence: 97%
“…M2 macrophages are associated with tissue repair/remodelling and allergic inflammation via the production of eotaxin in response to IL‐4/IL13, where both eotaxin and IL‐13 regulate eosinophilia and hallmark features of allergic inflammation . While higher M1 ratios in tissues are associated with pathogen clearance and neutrophilic inflammation, M2 skewing in asthma is generally associated with worsened eosinophilic inflammation and airway remodelling …”
Section: Introductionmentioning
confidence: 99%
“…Our results have translational significance because the management of patients with virus-induced asthma exacerbation remains a challenge. Further studies investigating new immunotherapeutic strategies that promote M1-like macrophage polarization, for instance, through TLR4 activation [69], prophylactic type I or type III IFN administration [70], or use of mebendazole may identify novel therapeutic strategies for this unmet medical need [71].…”
Section: Discussionmentioning
confidence: 99%
“…The role of macrophage polarization and activation during RSV infection is significant. In the asthmatic murine model, TLR-4 signaling linked to by RSV induced M1 activation and reduction in Th2-type cytokines [323]. Other studies have shown an opposite function where M2 macrophages in the lung of RSV-infected mice contribution to Th2-type cytokine production mediated by STAT6 [324,325] contributing to a protective role in RSV infection [326].…”
Section: Correlates Of Protectionmentioning
confidence: 99%